Improving the safety of hospital complexes in modern conditions - Ivanovich, Vaulin Vladimir; Aleksandrovich, Singeev Sergey (International Journal of Human and Health Sciences (IJHHS), 2021)
Background: The article presents the results of a study of ensuring fire safety in medical and preventive institutions (LPI) on the example of the central city hospital. Objectives: Research is aimed at improving the fire safety of hospital complexes and hospitals in modern conditions. Materials and Methods: The study used the methods of system analysis of scientific research and statistical data on ensuring fire safety, methods of structural analysis of the practice of ensuring fire safety of hospital complexes, mathematical methods for calculating the evacuation of people from a building and the spread of a fire in a building, methods for calculating the economic efficiency of means of support fire safety. Results and Discussion: Based on the analysis of fire statistics in healthcare facilities in Russia, it is concluded that it is advisable to improve the fire safety of hospitals and hospital complexes in modern conditions. The point of view is expressed that along with the fact that fire safety in hospitals is observed, the analysis indicates the existing problems in the practice of implementation. Conclusion: In order to increase the level of fire safety, it is possible to introduce: a modern fire alarm system; video of control systems and monitoring of safety of objects on the territory of the medical facility; installation of automatic fire extinguishing systems in fire-hazardous premises; installation of additional emergency lighting and reflectors indicating the direction of evacuation in case of fire and smoke; carrying out organizational and practical measures to ensure the safety of patients in a medical institution in an emergency situation (ES), namely, it is proposed to develop a memo of actions for patients in the hospital complex on inpatient treatment in case of an emergency with a list in the instruction log; provision of medical facilities with individual rescue equipment and provision of hospitals and hospital complexes with highrise buildings with modern evacuation means. International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 412-417